The Mother of All Wombs: Tracing the labour of maternal effacement in visual and theatrical cultures of motherhood. (19th May 2017) - Trezise, Bryoni
Abstract : This article traces a lineage across historical and contemporary performative cultures of motherhood: 19th century infant portraiture, contemporary viral news media and prenatal technology associated with the spectacle of digitised foetal sociality. Read together, these scenes depict a series of trajectories that map normative maternal subjectivities and their animation by, and embeddedness in, repertoires of visual culture. In different ways they work to secure the ontology of futurity that is attached to ideals of the child while erasing the maternal figure from view and imposing the vast machinery – the camera, Facebook – as central to the womb's perceived supplementarity. They show that in the contemporary context of the viral performativity of digital media, a maternallabour of effacement is specifically activated to present a new face of the future: the 'viral child'. The viral child, as a figure who is ostensibly able to give birth to itself, alienates the mother from the conditions of her reproductivity and instead stages itself as foundational to the neoliberal management of family life-worlds.